Solution-processed indium-zinc-oxide thin-film transistors based on anodized aluminum oxide gate insulator modified with zirconium oxide. Issue 63 (10th July 2015) - Li, Yuzhi; Lan, Linfeng; Xiao, Peng; Lin, Zhenguo; Sun, Sheng; Song, Wei; Song, Erlong; Gao, Peixiong; Wang, Dan; Ning, Honglong; Peng, Junbiao
<x xml:space="preserve">Abstract</x> Enhanced performance of solution-processed IZO-TFTs with ZrOx interlayer due to Al diffusion suppression.